P-641 Physicians' practices towards hormone monitoring during ovarian stimulation in context of treatment with Assisted Reproductive Technology (ART). A global Survey conducted through IVFworldwide.com. (30th June 2022) - Guedj, N. Sachs; Hart, R; Requena, A; Vergara, V; Polyzos, N.P
Abstract: Study question: What is the practice of routine hormone monitoring (HM) during ovarian stimulation (OS) in the context of ART treatment? Summary answer: The majority of ART specialists (∼80%) use HM, along with ultrasound, for monitoring OS, especially for the prevention of ovarian hyperstimulation syndrome (OHSS). What is known already: Ovarian stimulation (OS) is an essential part of ART and optimal monitoring is essential in order to optimize final outcome and ensure safety. Monitoring of OS can be either done with ultrasound (US) and/or hormonal monitoring in order to adjust gonadotropin dose, to trigger ovulation and to maximize success while avoiding the risk of OHSS. Clinical practice guidelines typically propose US monitoring as the cornerstone of OS monitoring during ART treatment. Although HM is practiced widely, the current attitude and practice of clinicians regarding HM has not been evaluated on a global scale. Study design, size, duration: In a cross-sectional study carried out using a survey on current practice of blood HM, we evaluated physicians' attitudes towards blood HM during OS in context of ART treatment. An open-access questionnaire was accessible to the members of IVF-Worldwide.com, from September 8 to October 13, 2021 on IVF-Worldwide.com and was completed by 528 participants. Data analysis was performed using Excel (Microsoft Inc., USA), statistics were calculated once giving all survey entries an equal representation. Participants/materials, setting, methods: An initial invitation and one reminder were sent to all 3845 registered members of IVF-Worldwide.com by email. In total, 528 participants answered the survey (13.7%). The survey was composed of 25 multiple-choice questions with mainly single answers. These questions asked about tests performed during any cycle monitoring visits during OS for ART treatment (blood hormone monitoring, ultrasound, timing, and frequency of prescribed tests), about monitoring to prevent OHSS as well as to adjust gonadotropin dose. Main results and the role of chance: A total of 528 members from 88 countries responded to this web-based survey. Most participants (87.9%) were clinicians and practiced reproductive medicine for more than 15 years (56.7%). Nearly half (46.2%) performed more than 500 oocyte aspiration cycles in their clinic annually. Of the 528 respondents, the vast majority (98.9%) used US to monitor OS cycles during ART treatment. Hormone monitoring (HM) was widely accepted and performed by 420 (79.5%) of participants during any of the cycle monitoring visits for OS (from stimulation day 1 until the day before ovulation triggering (OT)). Among different visits, participants most frequently monitored hormones on the day on or before the final oocyte maturation (71%) as compared with 57% on the first visit and 61% on the second and third visit during OS. The most frequent reason for HM was for prediction of OHSS (74%) and for adjusting gonadotropin dose (50%), whereas 45% of physicians considered HM for timing of OT. Most respondents (60.7%) considered that hormones play an important role in monitoring ovarian response during OS and a 58% considered that blood hormone tests are important to guiding decision-making in preventing OHSS. Limitations, reasons for caution: The survey was designed to represent self-reported statistics and opinions from experts in the field. It did not capture actual clinician performance or patient data. Wider implications of the findings: Although several guidelines consider US monitoring as the cornerstone for monitoring ovarian response during OS for ART, the majority of ART specialists consider HM as essential. Good quality studies are needed to document the value of HM during OS, with respect to dose adjustment, ovulation triggering and prevention of OHSS. Trial registration number: not applicable